2013
DOI: 10.1017/s1368980013002280
|View full text |Cite
|
Sign up to set email alerts
|

Mother's education is the most important factor in socio-economic inequality of child stunting in Iran

Abstract: Objective: Malnutrition is one of the most important health problems, especially in developing countries. The present study aimed to describe the socio-economic inequality in stunting and its determinants in Iran for the first time. Design: Cross-sectional, population-based survey, carried out in 2009. Using randomized cluster sampling, weight and height of children were measured and anthropometric indices were calculated based on child growth standards given by the WHO. Socio-economic status of families was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 19 publications
(30 reference statements)
5
28
0
4
Order By: Relevance
“…Asfaw et al findings also confirmed diarrhea (at the last two weeks), was significantly associated with stunting [30]. Our findings confirm Emamian et al results that showed mothers' education is the most important factors associated with stunting [31]. Although mother' education was not associated with underweight based on our results, in order to improve physical growth of children aged 6 to 24 months, educational programs targeting on to enhance the mothers' education level seems effective.…”
Section: Discussionsupporting
confidence: 90%
“…Asfaw et al findings also confirmed diarrhea (at the last two weeks), was significantly associated with stunting [30]. Our findings confirm Emamian et al results that showed mothers' education is the most important factors associated with stunting [31]. Although mother' education was not associated with underweight based on our results, in order to improve physical growth of children aged 6 to 24 months, educational programs targeting on to enhance the mothers' education level seems effective.…”
Section: Discussionsupporting
confidence: 90%
“…Among the mentioned variables, mother's education was the most contributing factor in the explained component (62% of the explained component and 27% of the total gap); thus, the low socioeconomic group was more sensitive to changes in mother's education. Other studies also showed that infant mortality rate was higher in low-educated mothers (18, 19). Our results indicated that infant mortality rate decreased as birth weight increased.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, infants' morbidity and mortality could be prevented by breastfeeding promotion, especially in low socioeconomic groups. The Oaxaca decomposition method has been used in different health fields around the world (19, 27-29). However, for child mortality, this method has only been used by Van de Poel et al (30).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration index takes a negative value when the curve lies above the line of equality, indicating that the health variable is concentrated in the non‐affluent group (that is the low‐income families in the present study). The index takes a positive value when the variable is concentrated in the affluent group (that is the high‐income families in the present study) …”
Section: Methodsmentioning
confidence: 84%